Sertaconazole: an antifungal agent for the topical treatment of superficial candidiasis. Issue 4 (April 2013) - Carrillo-Muñoz, Alfonso Javier; Tur-Tur, Cristina; Giusiano, Gustavo; Marcos-Arias, Cristina; Eraso, Elena; Jauregizar, Nerea; Quindós, Guillermo
Sertaconazole is a useful antifungal agent against mycoses of the skin and mucosa, such as cutaneous, genital and oral candidiasis and tinea pedis. Its antifungal activity is due to inhibition of the ergosterol biosynthesis and disruption of the cell wall. At higher concentrations, sertaconazole is able to bind to nonsterol lipids of the fungal cell wall, increasing the permeability and the subsequent death of fungal cells. Fungistatic and fungicidal activities on Candida are dose-dependent. The antifungal spectrum of sertaconazole includes deramophytes, Candida, Cryptococcu s, Malassezia and also Aspergillus, Scedosporium and Scopulariopsis. Sertaconazole also shows an antimicrobial activity against streptococci, staphylococci and protozoa ( Trichomonas ). In clinical trials including patients with vulvovaginal candidiasis, a single dose of sertaconazole produced a higher cure rate compared with other topical azoles such as econazole and clotrimazole, in shorter periods. Sertaconazole has shown an anti-inflammatory effect that is very useful for the relief of unpleasant symptoms